2010
DOI: 10.22401/jnus.13.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Levels in Serum and Cervicovaginal Secretions of Patients Infected With Trichomonas Vaginalis

Abstract: Background: Trichomoniasis caused by Trichomonas vaginalis, is one of the most common sexually transmitted parasites in the world, accounting for approximately 170 million infections annually. Although the factor behinds such incidence is still not clear, local and systemic host immune response is involved. Objectives: Accordingly, the present research was planned to determine the level of immunoglobulins (IgA, IgG and IgM) in sera and vaginal washes of women infected with T. vaginalis. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…The results of the current study also showed a significant increase in the level of IgG in the serum of women infected with T. vaginalis compared to the control group (8.16 ± 2.20 ng/dl), (6.53 ± 1.69 ng/dl). This result is consistent with (14) who found, through their studies, a high level of IgG in the serum of mice infested with the parasite compared to the control group as well as with (17) who demonstrated through their study a rise in the level of IgG in the serum of women infected with parasite compared to the control group, which indicates that chronic infections are common especially in married women due to repeated infection and leave it without treatment .Moreover, to the fact that most of the infected women are asymptomatic when infected with T. vaginalis. In addition to what has been mentioned, the role of immunoglobulin, especially IgG, has a significant role in humoral immunity to control the parasitic infection (18) .…”
Section: Estimation Of Immunoglobulin Levels Igm Lgg Andsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the current study also showed a significant increase in the level of IgG in the serum of women infected with T. vaginalis compared to the control group (8.16 ± 2.20 ng/dl), (6.53 ± 1.69 ng/dl). This result is consistent with (14) who found, through their studies, a high level of IgG in the serum of mice infested with the parasite compared to the control group as well as with (17) who demonstrated through their study a rise in the level of IgG in the serum of women infected with parasite compared to the control group, which indicates that chronic infections are common especially in married women due to repeated infection and leave it without treatment .Moreover, to the fact that most of the infected women are asymptomatic when infected with T. vaginalis. In addition to what has been mentioned, the role of immunoglobulin, especially IgG, has a significant role in humoral immunity to control the parasitic infection (18) .…”
Section: Estimation Of Immunoglobulin Levels Igm Lgg Andsupporting
confidence: 91%
“…The results of the current study also showed a significant increase in the level of IgA in the serum of women with T. vaginalis compared to the control group (8.22 ± 3.1ng/dl), (7.82 ± 2.8 ng/dl), respectively, and this result is consistent with (18) as well as with (17) , As our study showed that there are no significant differences between the patients and the control group, and the reason for this result is that IgA rises in acute cases of the disease and returns to its normal level in chronic cases, and because most of the cases with T. vaginalis are chronic cases as mentioned Above. As the immune response depends on humoral immunity and begins as a local inflammation at the place of invasion and pathogen presence, WBC is attracted to the site of infection and produces cytokines, which in turn stimulate the production of specific immunoglobulins, especially IgA, which is considered one of the main media specialized in host defenses present in the secretions.…”
Section: Estimation Of Immunoglobulin Levels Igm Lgg Andsupporting
confidence: 87%